Association between EGFR gene polymorphisms, skin rash and response to anti‐EGFR therapy in metastatic colorectal cancer patients. Issue 10 (October 2014) - Jaka, Ane; Gutiérrez‐Rivera, Araika; Ormaechea, Nerea; Blanco, Jesus; La Casta, Adelaida; Sarasqueta, Cristina; Izeta, Ander; Tuneu, Anna
Abstract Cetuximab and panitumumab are epidermal growth factor receptor (EGFR) inhibitors used in metastatic colorectal cancer (mCRC). Most patients develop a papulopustular rash that may predict tumor response to treatment. EGFR gene polymorphisms may also determine tumor response and appearance of skin rash. We hypothesized an association between EGFR gene polymorphisms, papulopustular rash and response to anticancer treatment. Four EGFR polymorphisms (−216, −191, CA‐SSR, R521K) were analysed in 51 patients with mCRC receiving anti‐EGFR. Severity of cutaneous rash and tumor response was measured following standard scales. We report an association between SNP‐216 and tumor response (P = 0.003): no tumor progression occurred in TT genotype. Moreover, 92.3% of the responder patients developed skin rash, 62.9% of them presenting a grade ≥2 (P = 0.015). Thus, although underpowered, our preliminary data suggest that SNP‐216 polymorphism of the EGFR gene could be useful in predicting tumor response and the appearance of severe skin rash might also be associated.